Higher education landscape 2030 : A trend analysis based on the ahead international horizon scanning (2020)
Between February 2018 and January 2019, a systematic analysis of current trends and requirements in the areas of knowledge and competence was carried out within the project “(A) Higher Education Digital (AHEAD)—International Horizon Scanning/Trend Analysis on Digital Higher Education.” One aim of this project was to examine the latest developments in learning theory, didactics, and digital-education technology against the background of (increasingly) digitized higher education. The analysis formed the basis for a horizon scanning of higher education in 2030, designed to develop future scenarios that would meet future higher education demands by taking advantage of social and digital innovations. This study was conducted on behalf of the German Federal Ministry of Education and Research (BMBF) by the FiBS Research Institute for the Economics of Education and Social Affairs together with the HIS Institute for Higher Education Development e.V. (HIS-HE). The AHEAD study was commissioned to look into the future and reveal what the higher education landscape could look like in 2030. The study takes account of technological developments in society, without seeing them as the sole force driving future higher education. Rather, it assumes that higher education will change by 2030 as a result of developments in the following areas: – Knowledge and competence requirements from industry and social changes, in an increasingly digitalized world; – New developments in didactics, reflecting current discussions in the field of didactics and learning theory; – Digital technologies and new ways of using these technologies, which are likely to create new forms of learning and environments for learning. This study was conducted in two phases. First, preliminary studies were carried out to investigate the three areas mentioned above, using literature evaluations, surveys, interviews, and subsequent discussions with the AHEAD International Advisory Board.